Multi-View Spatial–Temporal Graph Neural Network for Traffic Prediction - Li, He; Jin, Duo; Li, XueJiao; Huang, HongJie; Yun, JinPeng; Huang, LongJi (Computer journal, 2023)
Abstract Spatial–temporal graph neural network has drawn more and more attention in recent years and is widely used to various real-world applications. However, learning the spatial–temporal graph neural network structure presents unique challenges including: (i) the dynamic spatial correlation; (ii) the dynamic temporal correlation. Even the existing methods take into account the spatial correlation, they still learn the static road network structure information, which cannot reflect the dynamic of road relations. Some of the works has focused on modeling the long-term time series, but the improvements have been limited tightly. To overcome these challenges, we proposed a novel approach called Multi-View Spatial–Temporal Graph Neural Network. Differ from the existing research, we designed a multi-view temporal transformer module to extract dynamic temporal correlation and enhance the expression of medium and long-term temporal features. We propose a multi-view spatial structure and a corresponding multi-view graph convolutional module, which are capable of simultaneously combining the features of static road network structure and dynamic changes. Compared with 11 baselines, our proposed model has achieved significant improvement in the accuracy of prediction.